Active aging: retrofitting housing and the environment for older African immigrant adults - Onanuga, Omotayo Adebayo (Kansas State University, 2023)
This comprehensive research explores the multifaceted relationship between housing environments and active aging among African immigrant older adults residing in the south side of Chicago. With a focus on promoting physical activity and improving the quality of life, this study delves into the perspectives, challenges, and opportunities faced by this demographic group in their residences and environment. The study’s foundation lies in a detailed review of existing literature investigating the impact of housing designs on the health and well-being of older adults. Various factors influencing physical activity among older African immigrants are meticulously examined, including housing affordability, mobility options, social elements, access to community services, and communication strategies. The research employs a robust methodology, including interviews and observations to collect firsthand insights from African immigrants aged 50 and above. The participants’ experiences are analyzed through the lens of active aging measures, encompassing housing, interaction with outdoor spaces, social participation, transportation, respect, social inclusion, communication, community support, health services, and civic participation. These measures serve as a framework, illuminating the intricate interplay between housing environments and the active aging process. A significant portion of the study concentrates on the housing challenges faced by the participants. Affordability emerges as a crucial concern, shaping their choices and opportunities. The research underscores the importance of diverse and innovative housing options across income levels, integrating age-friendly features and universal design principles. Additionally, the study highlights the significance of suitable, affordable, and safe public transportation, emphasizing the need for connectivity with key destinations to facilitate mobility. Furthermore, the study delves into the social aspects of active aging, emphasizing social inclusion, intergenerational interactions, and opportunities for participation and employment within the community. It explores the role of community activities and volunteering in fostering social capital and combatting social exclusion among African immigrant older adults. The findings of this study carry significant implications for policymakers, urban planners, and community developers. By understanding the unique challenges faced by African immigrant older adults, tailored interventions can be designed to create age-friendly housing environments that promote physical activity, social engagement, and overall well-being. This research not only offers significant contributions to the field of gerontology but also advocates for inclusive and culturally sensitive approaches to enhance the active aging experience for diverse immigrant populations. In conclusion, this study illuminates the complex relationship between housing environments and active aging among African immigrant older adults. By addressing the specific needs and challenges faced by this demographic group, this research lays the foundation for informed and targeted strategies. These strategies empower older immigrants to lead active, fulfilling lives in their adopted communities, marking a pivotal step toward a more inclusive and supportive aging society.
Keywords: Active aging; Housing; Older adult; African immigrants